Paragonimiasis in tuberculosis patients in Nagaland, India. Issue 1 (1st December 2016) - Das, Mrinalini; Doleckova, Katerina; Shenoy, Rahul; Mahanta, Jagadish; Narain, Kanwar; Devi, K. Rekha; Konyak, Tongmeth; Mansoor, Homa; Isaakidis, Petros
Abstract : Background: One of the infections that mimic tuberculosis (TB) is paragonimiasis (PRG), a foodborne parasitic disease caused by lung flukes of the genus Paragonimus . In the northeastern states of India, TB and PRG are endemic; however, PRG is rarely included in the differential diagnosis of TB. Objective: To address limited evidence on the dual burden of TB and PRG in northeastern India, we aimed to document the prevalence of PRG among TB patients using sputum smear, stool examination for children <15 years and ELISA. Design: A cross-sectional study of patients receiving TB treatment in the Médecins Sans Frontières (MSF)-supported TB programme in Mon district, in collaboration with the Regional Medical Research Centre (RMRC), Dibrugarh, Assam, between November 2012 and December 2013. Results: Of 96 patients screened between November 2012 and December 2013, three (3%) had pulmonary PRG and were successfully treated with praziquantel. Conclusions: PRG should be considered in the TB diagnostic algorithms in PRG–TB dual burden areas. In case of TB–PRG co-infection, it is preferable to treat PRG first followed by anti-TB treatment a few days later.